Lithology and Genesis of Late Cenozoic Deposits of Bajo Del Durazno, La Pampa Province, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Bajo del Durazno (65°10' - 65°30'O y 36°33' - 36°45'S, Loventué Departament, Figs. 1 and 2) is a transitional landscape area between two major phisiographic subregions: Subregion of Hills and Meadows (Subregión de las Colinas y Lomas) and Subregion of Plateaux and Valleys (Subregión de las Mesetas y Valles,) which dominate the central-northeastern and middle-eastern part of La Pampa Province (INTA, 1980). At present Bajo del Durazno is a closed drainage system forming a minor geomorphic unit within a regional longitudinal depression, which together with several other depressions run across an extensive structural plain. These longitudinal depressions are known as Valles transversales (Calmels, 1996).This paper reports the sedimentary characteristics of the deposits outcropping in the western part of Bajo del Durazno (Fig. 1). A lithofacies analysis approach was followed to describe and interpret the sedimentary processes involved in the accumulation of the sediments, the environment and the source area of the deposits. The general purpose is to shed light on the geological evolution of the depression.Bajo del Durazno is excavated in reddish brown sandy silts capped by a calcrete crust (Cerro Azul Formation, late Miocene) which outcrop along the southern and western margin of the depression (Figs.3 and 4). The deposits of Bajo del Durazno were studied in three main elevation systems of the western sector and the depression floor (Mehl y Zárate, 2006).The deposits outcropping in the three elevations system (I, II y III) comprise a fluvial facies association composed of clast supported gravels with planar crossbedded (lithofacies Gp); gravel with tangential crossbedded (lithofacies Gt); massive gravels (lithofacies Gcm); massive matrix supported gravels (lithofacies Gmm); silty sands with dispersed carbonate clasts (lithofacies Sm1); and massive sandy silts (lithofacies Fm2). The deposits are believed to be accumulated by ephemeral fluvial streams transporting fine sediments (suspended load) as well as bed loads (gravel and coarse sands). The variations of sedimentary structures in gravel lithofacies (Figs. 5 and 6) would reflect changes in flow hydraulic conditions.In the depression floor, the deposit consists of massive sandy silts with angular blocky fracturing and carbonate nodules (lithofacies Fm1), representing paludal- like environments (Fig. 10). The outcrops of lithofacies Fm1 located at higher topographic positions suggest a larger extension of the water body (paludal environment) prior to the accumulation of deposits in elevation system III and after the accumulation of deposits in elevation system II.Chronologically, the studied deposits are younger than the late Miocene represented by the Cerro Azul Formation and older than the eolian cover of the Meaucó Formation (Late Pleistocene-Holocene). The relative ages attributed to the sediments are based on their geomorphological location with the oldest cropping out in system elevation I and the youngest at the present floor of the depression.Geomorphologically the studied area of Bajo del Durazno reproduces a piedmont system at a local spatial scale. The elevation systems represent different piedmont levels (Mehl and Zárate, 2006), corresponding to a Bajada environment located between the flank pediments developed on the margin and the playa area (depression floor) (Fig. 11). The sediments of this bajada were deposited by ephemeral low sinuosity braided flows. These streams eroded the crust and sandy silts including carbonate nodules of the Cerro Azul Formation transporting the material from the surrounding tertiary outcrops to lower topographic positions within Bajo del Durazno (Mehl and Zárate, 2006).
Keywords: Fluvial deposits; Calcrete gravels; Piedmont; Late Cenozoic; La Pampa; Argentina.